1971
DOI: 10.1139/y71-047
|View full text |Cite
|
Sign up to set email alerts
|

The Further Purification of Motilin, a Gastric Motor Activity Stimulating Polypeptide from the Mucosa of the Small Intestine of Hogs

Abstract: BROWN, J. C., MUTT, V., and DRYBURGH, J. R. 1971. The further purification of motilin, a gastric motor activity stitnulating polypeptide from the mucosa of the small intestine of hogs. Can. J. Physiol. Pharmacol. 49,[399][400][401][402][403][404][405] A polypeptide has been isolated from the duodenal mucosa of hogs and has been named motilin. Motilin stimulates motor activity in both antral and fundic gland area pouches of the stomach of dogs. Pt will stimulate pepsin output, with no change in H' secretion, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
65
0
6

Year Published

1980
1980
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(73 citation statements)
references
References 8 publications
2
65
0
6
Order By: Relevance
“…Motilin, a 22 amino acid peptide, originally isolated from porcine duodenal mucosa (BROWN et al, 1971), stimulates enteric smooth muscle locally (BROWN et al, 1971;ITOH, 1976;CHRISTOFIDES et al, 1979). It has been well established that motilinimmunoreactive cells are one of the major endocrine cell types in the proximal small intestine of mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Motilin, a 22 amino acid peptide, originally isolated from porcine duodenal mucosa (BROWN et al, 1971), stimulates enteric smooth muscle locally (BROWN et al, 1971;ITOH, 1976;CHRISTOFIDES et al, 1979). It has been well established that motilinimmunoreactive cells are one of the major endocrine cell types in the proximal small intestine of mammals.…”
Section: Discussionmentioning
confidence: 99%
“…A significant negative correlation between MLI and IRI concentrations (r = -0.72, p <0.01) was observed. The present results indicate that the suppressive effect of insulin on motilin release is a direct action of insulin and is not mediated by glucose.insulin ; motilinMotilin, a 22 amino-acid peptide hormone has been known as one of the gut hormones which affect the motility of the stomach and intestine (Brown et al 1971;Lee et al 1974;Jennewein et al 1975). It has been shown that intraduodenal administration of glucose and amino-acids solution, which increase insulin release, inhibit the release of endogenous motilin (Christofides et al 1979).…”
mentioning
confidence: 64%
“…Motilin, a 22 amino-acid peptide hormone has been known as one of the gut hormones which affect the motility of the stomach and intestine (Brown et al 1971; Lee et al 1974;Jennewein et al 1975). It has been shown that intraduodenal administration of glucose and amino-acids solution, which increase insulin release, inhibit the release of endogenous motilin (Christofides et al 1979).…”
mentioning
confidence: 99%
“…When motilin, a 22amino acid polypeptide, was originally discovered and isolated from the hog duodenal mucosa by Brown et al in 1971, this hormone candidate was considered as an exciting agent that stimulates the contraction of gastric fundus in dog. As synthetic porcine motilin or its analogues had become available, its biological actions on the gastrointestinal tract were investigated by various groups of workers.…”
mentioning
confidence: 99%
“…Motilin, given intravenously, stimulates contraction of the canine stomach (Brown et al, 1971;Jennewein et al, 1975 ;Lee et al, 1974), lower esophageal sphincter (Jennewein et al, 1975 ;Gutierrez et al, 1977, Meissner et al, 1976, and small intestine (Jennewein et al, 1975 ;Lee et al, 1974). Motilin was also shown to increase the number of spike potentials of myoelectric activity in the canine antrum and small intestine (Castresana et al, 1978 ;Wingate et al, 1976).…”
mentioning
confidence: 99%